Simple decision-making model for orchard air-assisted spraying airflow - Wang, Xiang; Feng, Yuru; Fu, Wei; Qi, Jiangtao; Song, Jianli (International Journal of Agricultural and Biological Engineering, 2023)
Airflow speed is one of the three factors of air-assisted spraying. Optimizing the matching model between airflow speed and target canopy characteristics is an effective way to improve the orchard precision spraying technology, as airflow can significantly affect droplet deposition and drift loss. A simple model of airflow speed was established in this study. First, air-assisted spraying experiments were carried out on a standard simulation canopy to study the airflow speed depended on canopy width, leaf area index, and porosity rate. Second, determined by Ribbon Method and verified by droplet drift data, the airflow speed through the canopy was between 0.5 m/s and 0.7 m/s. Third, multiple tests were carried out under standard simulation canopy with different characteristics, and the airflow speed model was established ultimately: with a fixed leaf area index (LAI), the relationship between canopy upwind boundary airflow speed and canopy width satisfied the exponential model (y=aebx), and the coefficients a and b are well related to the density of branches and leaves in the canopy. When LAI=3.456, y=2.036e1.5887x, R2=0.994; LAI=1.728, y=1.639e1.445x, R2=0.972. Orchard growers can acquire needed airflow speed through this simple model, it is quick and precise and appropriate to most growth periods of a variety of fruit trees, such as apples, pears, and vines. Keywords: airflow speed, canopy width, porosity rate, LAI, air-assisted spraying DOI: 10.25165/j.ijabe.20231602.6849 Citation: Wang X, Feng Y R, Fu W, Qi J T, Song J L. Simple decision-making model for orchard air-assisted spraying airflow. Int J Agric & Biol Eng, 2023; 16(2): 23-29.